Analisis Kelayakan Finansial Usaha Penangkar Bibit Tanaman Buah Mangga Dengan Teknik (Grafting) Terhadap Pendapatan Produsen - Imam Fauzi Harahap; Gustami Harahap; Yusniar Lubis (Universitas Medan Area, 2023)
To find out the amount of production costs, revenue, income from the business of cultivating mango fruit seeds to producer income and to analyze the level of financial feasibility of the business of breeding mango fruit plants to producer income. and to determine the feasibility of a mango seedling breeder business using the R/C and B/C data analysis method. The results of this study are that the average total cost of a mango seed breeder business is IDR 145,216,627/year. The average income earned by the mango fruit plant breeder business is IDR 197,628,571/year so that the income obtained from the mango fruit plant seed breeder business is IDR 52,411,944/year. The financial feasibility analysis shows that if you look at the R/C value, this business is feasible because the R/C value is 1, which is 1.36 and if you look at the Net B/C value, this business is not feasible to be cultivated because the Net B/C value 1, which is equal to 0.36, means it is smaller than 1. So, the business of cultivating mango plant seeds is not feasible to be cultivated or run but provides little profit for entrepreneurs